2007
DOI: 10.1038/sj.onc.1210472
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of WNT5A, CRIP1 and S100P in prostate cancer

Abstract: Oligoarray analysis of a matched pair of prostate cancer and normal cell lines derived from the same radical prostatectomy specimen identified 113 candidate hypomethylated genes that were overexpressed in the cancer cells and contained CpG islands. Hypomethylation of wingless-related MMTV integration site 5A (WNT5A), S100 calcium-binding protein P (S100P) and cysteine-rich protein 1(CRIP1) was confirmed in the cancer cells by bisulfite sequencing. Treatment of the corresponding normal prostate epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 34 publications
8
85
0
1
Order By: Relevance
“…It has been shown that Wnt5a is upregulated at the transcriptional level in PCa by hypomethylation in the 5 0 -untranslated region and that three CpG sites were consistently methylated in normal tissues but not in primary PCa (Wang et al, 2007). It was also reported that membrane type 1-MMP is upregulated in PCa species and that membrane type 1-MMP-induced phenotypic changes are dependent on the expression of Wnt5a (Cao et al, 2008).…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcamentioning
confidence: 99%
“…It has been shown that Wnt5a is upregulated at the transcriptional level in PCa by hypomethylation in the 5 0 -untranslated region and that three CpG sites were consistently methylated in normal tissues but not in primary PCa (Wang et al, 2007). It was also reported that membrane type 1-MMP is upregulated in PCa species and that membrane type 1-MMP-induced phenotypic changes are dependent on the expression of Wnt5a (Cao et al, 2008).…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcamentioning
confidence: 99%
“…Overexpression of S100P was observed in various cancers, including pancreatic (5), breast (6), colon (7), prostate (8) and lung carcinomas (9). S100P was also reported to correlate with tumor growth and metastasis in breast (6,10,11), colon (12) and pancreatic (3) cancer.…”
Section: +mentioning
confidence: 99%
“…Normalization of androgen independent prostate tumors and is also associated with anti-apoptotic function of WNT5A. [27][28][29] A critical importance of calcium influx inhibition in reversing the docetaxel and multi-drug resistant phenotype was recently demonstrated in human lung cancer cell lines. 30 Taken together, our efforts to identify specific genes and molecular cascades mediating resistance to docetaxel in prostate cancer cells have yielded a narrow set of genes and associated specific cellular processes that appear highly relevant.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%